The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/healthcare10122410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flap Design on the Periodontal Health of Second Lower Molars after Impacted Third Molar Extraction

Abstract: The purpose of this study was to compare the envelope flap and triangular flap for impacted lower third molar (M3) extraction and their effects on the periodontal health of adjacent second molars (M2). A population of 60 patients undergoing M3 extraction with the envelope flap (Group A) or triangular flap (Group B) was analyzed, comparing probing pocket depth (PPD), clinical attachment level (CAL), and gingival recession (REC) recorded at six sites (disto-lingual, mid-lingual, mesio-lingual, disto-vestibular, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Furthermore, the formation of a periodontal pocket distal to the adjacent second molar is the most common and well-known post-operative complication, as described by many authors. Although a direct correlation between pain, tumefaction, probing depths, and bleeding on probing was not established, it appears that younger patients are less prone to develop periodontal pockets, and generally, the probing depths are significantly lower compared to adult patients [ 19 , 20 , 21 , 22 , 29 ]. In our study, a higher probing depth was observed in patients treated with a marginal approach.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the formation of a periodontal pocket distal to the adjacent second molar is the most common and well-known post-operative complication, as described by many authors. Although a direct correlation between pain, tumefaction, probing depths, and bleeding on probing was not established, it appears that younger patients are less prone to develop periodontal pockets, and generally, the probing depths are significantly lower compared to adult patients [ 19 , 20 , 21 , 22 , 29 ]. In our study, a higher probing depth was observed in patients treated with a marginal approach.…”
Section: Discussionmentioning
confidence: 99%
“…Extraction of third molars represents a frequently invasive surgical procedure for both hard and soft tissues, particularly in the lower jaw. As the design of the access flap, gingival detachment included, often implicates a considerable damage for the entire periodontium, periodontal healing seems to depend on the chosen surgical technique [1]. Additional factors influencing the quality and course of the healing process must be taken into consideration, including the patient's age, patient's systemic conditions and eventual medications taken, periodontal conditions of the adjacent second molar, position of the third molar and inclination of its roots, relationship between the third molar and the inferior alveolar nerve, relationship between the third molar and the second molar, and the degree of openness of the patient's mouth [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%